ANALISIS PENERAPAN AUDIT MANAJEMEN ATAS FUNGSI KEUANGAN PADA PT. WESITAN KONSULTASI PEMBANGUNAN DI MAKASSAR - Ibrahim Ahmad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The problem in this study is whether the implementation of a management audit of the financial functions at PT Wesitan Development Consultancy in Makassar has been instrumental in increasing the efficiency and effectiveness of the company. To solve these problems we used descriptive analysis method, namely the researcher describes the application of a management audit of the financial function in PT Wesitan Consultancy Development consisting of a general description of the financial function, Preliminary investigation, verification and testing of controls management, audit findings and making reports and documentation, using the techniques of data collection through: observation, interview and documentation. The results of the analysis found that based on the results of the preliminary analysis of the survey shows that managing cash flow has not been done efficiently and effectively, the reason being to manage cash flow efficiently and effectively is still no definitive management of cash flow. From the analysis of the verification and testing of management control in a company is often seen that there is difference between budget receipts and expenditures with actual cash in the company and in addition the company is less effective in completing the project. The results of the analysis of audit findings for the functioning of financial inefficiency cash flow management by the company because the company does not resolve cash flow effectively and in addition project control system that is not right.